Bacterial resistance to silver nanoparticles and how to overcome it - Panáček, Aleš; Kvítek, Libor; Smékalová, Monika; Večeřová, Renata; Kolář, Milan; Röderová, Magdalena; Dyčka, Filip; Šebela, Marek; Prucek, Robert; Tomanec, Ondřej; Zbořil, Radek (Nature nanotechnology, 2018)
Silver nanoparticles have already been successfully applied in various biomedical and antimicrobial technologies and products used in everyday life. Although bacterial resistance to antibiotics has been extensively discussed in the literature, the possible development of resistance to silver nanoparticles has not been fully explored. We report that the Gram-negative bacteria Escherichia coli 013, Pseudomonas aeruginosa CCM 3955 and E. coli CCM 3954 can develop resistance to silver nanoparticles after repeated exposure. The resistance stems from the production of the adhesive flagellum protein flagellin, which triggers the aggregation of the nanoparticles. This resistance evolves without any genetic changes; only phenotypic change is needed to reduce the nanoparticles' colloidal stability and thus eliminate their antibacterial activity. The resistance mechanism cannot be overcome by additional stabilization of silver nanoparticles using surfactants or polymers. It is, however, strongly suppressed by inhibiting flagellin production with pomegranate rind extract.
Keywords: Metal Nanoparticles; antibakteriální látky; stabilita léku; Anti-Bacterial Agents; Drug Resistance, Bacterial; kovové nanočástice; Silver; Escherichia coli; Microbial Sensitivity Tests; Pseudomonas aeruginosa; mikrobiální testy citlivosti; Drug Stability; bakteriální léková rezistence; stříbro